An improved, non-isotopic method of screening cells from patients with abnormalities of sexual differentiation for Y chromosomal DNA content. Issue 4 (April 1993) - Witt, M; Michalczak, K; Latos-Bielenska, A; Jaruzelska, J; Kuczora, I; Lopez, M
Abstract : The detection of 45, X/46, XY mosaicism in patients with abnormalities of sexual differentiation is of crucial diagnostic importance. Here we present application of a PCR based method of detection of alphoid repeats of Y chromosomal origin. The method detects 0.01% of male DNA on a female DNA background. Out of 28 patients studied, in all cases where the Y chromosome or a part of it containing centromeric sequences was present, a positive amplification signal of Y chromosomal alphoid repeats was detected. In five cases the Y origin of marker chromosomes was diagnosed. The pattern of amplification signal distribution of the SRY gene was identical to that of Y specific alphoid primers, which confirms applicability of this method in the molecular diagnostic laboratory. The other diagnostic advantage is the ability to use dried blood specimens as an easy to handle and efficient source of DNA.